PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN BERBICARA BAHASA INDONESIA SISWA KELAS VI SEKOLAH MADRASAHIBTIDAIYAH PANGERAN HIDAYATULLAH [Vocabulary Mastery of the Ability to Speak Indonesia Students of Class VI School of Madrasah Ibtidaiyah Pangeran Hidayatullah] - Hestiyana Hestiyana (TOTOBUANG, 2019)
This study aims to describe the mastery of  Indonesian vocabulary and the ability to speak Indonesianstudents of class VI school of Madrasah Ibtidaiyah Pangeran Hidayatullah. This research uses quantitativedescriptive research. The object of this research was students of class VI school of Madrasah IbtidaiyahPangeran Hidayatullah with a saturated sampling technique. Instruments used in data collection, namely:test sheets, observation guidelines, and documentation. Data analysis was performed using descriptivestatistical analysis. Based on the results of the analysis, it can be seen that the mastery of Indonesianvocabulary and the ability to speak Indonesian in students of class VI school of Madrasah IbtidaiyahPangeran Hidayatullah are in the moderate category. Mastery of Indonesian vocabulary has an averagevalue of 24.40 which is in the interval 23-24 so it can be stated that the mastery of Indonesian vocabularyof students is in the medium category. Then, the ability to speak Indonesian in students of class VI schoolof Madrasah Ibtidaiyah Pangeran Hidayatullah was in the moderate category with an average value of 10.08in intervals of 10-11 so that students' speaking ability was in the medium category. Penelitian ini bertujuan mendeskripsikan penguasaan kosakata bahasa Indonesia dan kemampuan berbicara bahasa Indonesia siswa kelas VI Sekolah Madrasah Ibtidaiyah Pangeran Hidayatullah. Penelitian ini menggunakan jenis penelitian deskriptif kuantitatif. Objek penelitian ini adalah siswa kelas VI Sekolah Madrasah Ibtidaiyah Pangeran Hidayatullah dengan teknik pengambilan sampel jenuh. Instrumen yang digunakan dalam pengumpulan data, yaitu: lembar tes, pedoman observasi, dan dokumentasi. Analisis data dilakukan dengan menggunakan analisis statistik deskriptif. Berdasarkan hasil analisis dapat diketahui bahwa penguasaan kosakata bahasa Indonesia dan kemampuan berbicara bahasa Indonesia siswa kelas VI Sekolah Madrasah Ibtidaiyah Pangeran Hidayatullah berada pada kategori sedang. Penguasaan kosakata bahasa Indonesia memiliki nilai rata-rata sebesar 24,40 yang berada pada interval 23—24 sehingga dapat dinyatakan bahwa penguasaan kosakata bahasa Indonesia siswa berada pada kategori sedang. Kemudian, kemampuan berbicara bahasa Indonesia siswa kelas VI Sekolah Madrasah Ibtidaiyah Pangeran Hidayatullah berada pada kategori sedang dengan  nilai rata-rata sebesar 10,08 yang berada pada interval   10—11 sehingga dapat dinyatakan bahwa kemampuan berbicara siswa berada pada kategori sedang.